Religious and Cultural Relations (Cross-Cultural Counseling) - Syafi’ah, Nailis (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Humans as social beings (zoon politicon) in everyday life cannot be separated from religious and cultural elements, because the nature of humans is religious beings (homo religious). In addition, humans are also born as cultured human beings, but in the process of running a life, of course, problems will arise that arise in religion and culture, so an interfaith and cultural counseling process is needed. This research applies a qualitative approach using descriptive methods. The result of this scientific work is that religion and culture can influence each other. Religion influences cultural systems as well as the practices of life. On the contrary, culture can also influence religion. The behavior of Indonesian society is very diverse in implementing religious and cultural values in everyday life. Religion is a cultural system consisting of values that unite society and provide identity for the individual. In this case, religion through ceremonies imposes values on each individual and forms organic solidarity. They always seek to divide and refer in various ways to conflict in religious life. If we do not have the power of belief and faith, it will be easily influenced so that problems arise in ourselves and with others and can even spread to the community. This is the challenge for counselors in helping to overcome various kinds of problems experienced by individuals and groups. Culture has elements that include patterns of behavior, ideas and values, including religious values. Therefore, counselors should place their clients' religious values in a cross-cultural perspective. This means that in the process of counseling he must know some information about the life of the client. Information about certain religious values, as it is an important part of the counselor's preparation to understand the client's self in the counseling process.